2011
DOI: 10.1242/jcs.086710
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 is an important downstream component of BMP signalling in epidermal keratinocytes

Abstract: SummaryBone morphogenetic proteins (BMPs) play essential roles in the control of skin development, postnatal tissue remodelling and tumorigenesis. To explore whether some of the effects of BMP signalling are mediated by microRNAs, we performed genome-wide microRNA (miRNA) screening in primary mouse keratinocytes after BMP4 treatment. Microarray analysis revealed substantial BMP4-dependent changes in the expression of distinct miRNAs, including miR-21. Real-time PCR confirmed that BMP4 dramatically inhibits miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 42 publications
4
78
1
Order By: Relevance
“…Our results suggest that one mechanism underlying these effects of miR-21 on skin tumorigenesis is down-regulation of tumor suppressors and DNA repair genes such as MSH2. In addition to MSH2, our gene list of likely miR-21 targets identified several other genes that could contribute to tumorigenesis through cell cycle regulation and DNA repair (Figure 4a; Supplementary Table S2) (17, 46), the predominant processes affected by miR-21 perturbation in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that one mechanism underlying these effects of miR-21 on skin tumorigenesis is down-regulation of tumor suppressors and DNA repair genes such as MSH2. In addition to MSH2, our gene list of likely miR-21 targets identified several other genes that could contribute to tumorigenesis through cell cycle regulation and DNA repair (Figure 4a; Supplementary Table S2) (17, 46), the predominant processes affected by miR-21 perturbation in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact studies have also identified other factors including AP1 that can also drive up miR-21 in tumors (47), and BMP4 as an inhibitor of miR-21 expression in keratinocytes (17). Furthermore, miR-21 itself was recently shown to target Grhl3 (44), suggesting the possibility of a feed-forward autoregulatory loop between Grhl3 and miR-21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often a miRNA has hundreds of different target genes, regulating biological functions through the modulation of their expression (9,10). Several miRNAs have been identified to have important and specific functions in the skin, both in keratinocytes (11)(12)(13)(14)(15)(16) and in other cell types (17,18), showing the relevance of this class of molecules in skin biology.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological mechanism of hair growth is extremely complex requiring the coordinated regulation of many growth factors. MicroRNAs regulate animal hair growth by targeting growth factor genes (Ahmed et al, 2011;Yuan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%